2022
DOI: 10.3389/fnut.2022.910785
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-individual Differences in the Human Intestinal Microbial Conversion of (-)-Epicatechin and Bioactivity of Its Major Colonic Metabolite 5-(3′,4′-Dihydroxy-Phenyl)-γ-Valerolactone in Regulating Nrf2-Mediated Gene Expression

Abstract: (-)-Epicatechin (EC) is one of the most popular polyphenols present in various food products in daily life. Upon intake, it is intensively metabolized by microbiota in the large intestine. In the present study, intra- and inter-individual variations in this gut microbial conversion of EC and the concomitant formation of its major metabolites, including 5-(3′,4′-dihydroxy phenyl)-γ-valerolactone (3,4-diHPV), were identified and quantified via liquid chromatography triple quadrupole mass spectrometry (LC-TQ-MS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…EC and 3,4-diHPV both activate Nrf2-mediated gene expression, however, 3,4-diHPV shows higher potency in the upregulation of Nrf2 gene expression than EC. Conversion of EC to 3,4-diHPV by the gut microbiota improves the overall health-promoting effects of EC consumption due to this ability to selectively promote Nrf2 pathway activation [ 230 ].…”
Section: Vasodilatory Flavonoidsmentioning
confidence: 99%
“…EC and 3,4-diHPV both activate Nrf2-mediated gene expression, however, 3,4-diHPV shows higher potency in the upregulation of Nrf2 gene expression than EC. Conversion of EC to 3,4-diHPV by the gut microbiota improves the overall health-promoting effects of EC consumption due to this ability to selectively promote Nrf2 pathway activation [ 230 ].…”
Section: Vasodilatory Flavonoidsmentioning
confidence: 99%
“…Indeed, many works where the source of IIV was classified as “undefined” are likely related to differences in the gut microbiota composition, but evidence of this still has to be provided. Faecal fermentation studies may be of help in classifying individuals according to the microbial metabolism of specific phenolics, as recently done for some flavan-3-ol monomers and avenanthramides [ [163] , [164] , [165] ].…”
Section: Resultsmentioning
confidence: 99%
“…These two microflora-derived metabolites were included since they were reported to be more potent in triggering Nrf2-mediated gene expression than the parent compound EGCG in our previous study . However, given that other gut microbiota metabolites of EGCG such as, for example, phenylvalerolactones and phenylvaleric acids might also have biological activities, it may be of interest to include also these metabolites in future PBK model development. Previous studies showed a proof of the principle for the inclusion of gut microbial metabolism in PBK modeling using kinetic parameters derived from in vitro anaerobic fecal incubations. , The model predicted the C max of GA and PG, after consumption of two capsules of the EGCG supplement (the recommended daily intake), to be less than 1.5% of the blood C max of EGCG and less than 14.1% when expressed in unbound EGCG equivalents in plasma.…”
Section: Discussionmentioning
confidence: 99%